Best Practice Outcomes Based Education Islamic Religious Education Curricullum; Implementation and Challenges in Higher Education Tri Dharma Activities - Effendi, Muhamad Ridwan (International Conference on Islamic Studies, 2022)
Outcomes Based Education (OBE) curriculum is a curriculum concept that emphasizes the sustainability of the learning process in an innovative, interactive, and effective manner. The purpose of this article is to develop an outcome-based learning curriculum guideline. This study uses qualitative methods and follows the flow of research procedures, starting with the preliminary study stage, development stage, and evaluation stage. This study's data source is the academic community, including lecturers and students. Data collection in the preliminary study was carried out with several instruments, such as observation, interviews, and documentation studies. Curriculum experts carried out expert validation in this study. The results of this study indicate that the OBE curriculum applied in this results-based learning activity has been effective in increasing the output product in the form of the work of lecturers and students so that it is very suitable to be set as an academic policy as well as a guide in organizing lectures.